IMPROVING STUDENTS’ LEARNING OUTCOMES BY USING PICTURE MEDIA ON THE STRUCTURE AND FUNCTION OF PLANT PARTS - Yudi; Abira, Abrar (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Student learning outcomes on the science material on the Structure and Function of Plant Parts were 47 (low category). This was due to students' lack of awareness of the importance of understanding and mastering the material that had been presented, and also in teaching the teacher only delivered the material and students listened, took notes, and did practice questions. So a study was conducted that aimed to improve learning outcomes on the structure and function of plant parts using picture media for fourth-grade students of SDN Sawah Baru. This study used Classroom Action Research (CAR) with two-cycle learning improvements. The subjects in this study were 31 fourth-grade students with 11 boys and 20 girls. Data collection techniques used observation and tests. The results of the observations were analyzed using qualitative descriptive techniques and the results of the tests were analyzed using quantitative descriptive techniques. The findings of this study include: (1) the use of picture media in improving learning was very good, as evidenced by the APS-PKP 2 score of 97 (very good category),(2) Student learning outcomes in the learning improvement were very good, with a change in the average class score of 16 points. Originally in cycle 1 it was 64 (sufficient category) and in cycle 2 it was 80 (very good category), (3) The use of image media can improve student learning outcomes, with an increase in the class average from cycle 1 to cycle 2 of 16%. Thus, it can be concluded that the use of image media can improve leaning outcomes on the structure and function of plant parts for students at the UPTD SD Negeri Sawah Baru, South Tangerang City.